Interpersonal incomparability in citizens' views of democracy: survey evidence from Ukraine. Issue 2 (2nd April 2020) - Erlich, Aaron; Garner, Calvin
ABSTRACT: Do regional differences within a single country influence how survey respondents use response scales when evaluating concepts like democracy? Further, what determines how respondents will assess the level of democracy at home or abroad? We test three hypotheses to answer these questions. First, we hypothesize that differential item function (DIF) exists between regions that are most different along political, cultural, and historical dimensions. Second, we hypothesize that political attitudes will predict views about evaluations of the level of democracy domestically. Third, we hypothesize that regions with stronger ties to and greater affinity for a foreign state will rate that state as more democratic than other regions. We find support for all three hypotheses using a nationally representative survey of Ukraine, but correcting for DIF generates substantively important changes in our interpretations of the results. Specifically, it increases support for hypothesis two but leads to a more measured conclusion about hypothesis three. An analysis of the responses to anchoring vignettes to control for DIF provides some initial suggestive evidence that Ukrainians outside Kyiv may view democracy as more binary in nature than on a nuanced sliding scale. We conclude with recommendations for researchers on deploying anchoring vignettes in sub-national survey research.